Asteroid Compositions: some evidence from polarimetry - Cellino, A. (2007)
Although it cannot provide direct and unambiguous information on the mineralogical composition of an asteroid surface, polarimetry is a very useful tool to get an improved understanding of parameters which are intimately related to surface composition and regolith structure. In recent times there has been a revival in the field of asteroid polarimetry, on the theoretical side, in relation to experimental simulations, and due to the activity of some teams who are engaged in extensive observational campaigns. Some new discoveries of objects exhibiting unprecedented polarimetric properties have been done. The above subjects are briefly reviewed.